Ethical Mechanisms in Preventing Bureaucratic Corruption: A Comparative Study across Indonesian Government Institutions - Abdi Abdi; Hafiz Elfiansya Parawu; Nursaleh Hartaman (Journal of Government and Civil Society, 2025)
Bureaucratic corruption in Indonesia remains a serious problem despite the establishment of various oversight institutions since the 1998 Reform era. This article aims to analyze the role of ethical mechanisms in preventing bureaucratic corruption through a comparative study of three main institutions: Corruption Eradication Commission (KPK), Ombudsman of the Republic of Indonesia (ORI), and Inspectorate General (Itjen) within the ministry. This research uses a qualitative approach with literature study methods, analysis of official documents, and utilization of online data from credible sources. The findings show that the implementation of bureaucratic ethics plays a significant role in reducing the potential for corruptive behavior. KPK implements a strict internal code of ethics and manages various integrity strengthening programs such as the Integrity Assessment Survey (SPI) and Integrity Zone (ZI) to instill an anti-corruption culture within the government. ORI focuses on preventing maladministration and enforcing ethical standards in public services, which serves as a bulwark against petty corruption. Meanwhile, Itjen carries out the function of internal supervision and fostering the integrity of the state civil apparatus (ASN), although it faces challenges in terms of independence and limited resources. Comparatively, the three institutions complement each other. KPK has an advantage in terms of national prosecution and coordination, ORI excels in monitoring public service ethics, and Itjen plays a role in early detection of internal bureaucratic irregularities. Ethical mechanisms such as the implementation of a code of ethics, the development of an integrity system, and the implementation of ethics-based supervision have proven effective in improving accountability and preventing bureaucratic corruption.Korupsi birokrasi di Indonesia masih menjadi persoalan serius meskipun berbagai lembaga pengawas telah dibentuk sejak era Reformasi 1998. Artikel ini bertujuan untuk menganalisis peran mekanisme etik dalam mencegah korupsi birokrasi melalui studi komparatif terhadap tiga institusi utama: Komisi Pemberantasan Korupsi (KPK), Ombudsman Republik Indonesia (ORI), dan Inspektorat Jenderal (Itjen) di lingkungan kementerian. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur, analisis dokumen resmi, serta pemanfaatan data daring dari sumber yang kredibel. Temuan menunjukkan bahwa penerapan etika birokrasi berperan signifikan dalam mengurangi potensi perilaku koruptif. KPK menerapkan kode etik internal yang ketat serta mengelola berbagai program penguatan integritas seperti Survei Penilaian Integritas (SPI) dan Zona Integritas (ZI) guna menanamkan budaya antikorupsi di lingkungan pemerintah. ORI berfokus pada pencegahan maladministrasi dan penegakan standar etika pelayanan publik, yang menjadi benteng terhadap praktik korupsi kecil (petty corruption). Sementara itu, Itjen menjalankan fungsi pengawasan internal dan pembinaan integritas aparatur sipil negara (ASN), meskipun menghadapi tantangan pada aspek independensi dan keterbatasan sumber daya. Secara komparatif, ketiga institusi tersebut saling melengkapi. KPK memiliki keunggulan dalam hal penindakan dan koordinasi nasional, ORI unggul dalam pengawasan etika pelayanan publik, dan Itjen berperan dalam deteksi dini terhadap penyimpangan internal birokrasi. Mekanisme etik seperti penerapan kode etik, pembangunan sistem integritas, dan pelaksanaan pengawasan berbasis etika terbukti efektif dalam meningkatkan akuntabilitas dan mencegah korupsi birokrasi.